1982
DOI: 10.1073/pnas.79.15.4575
|View full text |Cite
|
Sign up to set email alerts
|

Human somatostatin I: sequence of the cDNA.

Abstract: RNA has been isolated from a human pancreatic somatostatinoma and used to prepare a cDNA library. After prescreening, clones containing somatostatin I sequences were identified by hybridization with an anglerfish somatostatin I-cloned cDNA probe. From the nucleotide sequence oftwo ofthese clones, we have deduced an essentially full-length mRNA sequence, including the preprosomatostatin coding region, 105 nucleotides from the 5' untranslated region and the complete 150-nucleotide 3' untranslated region. The co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
83
0
1

Year Published

1983
1983
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 233 publications
(86 citation statements)
references
References 24 publications
2
83
0
1
Order By: Relevance
“…10;Veber et al, 1979;Flohr et al, 2002;Labarrère et al, 2003;Chatenet et al, 2004), so that UII has been first described as a somatostatin-like peptide (Pearson et al, 1980). In addition, it has been found that the organization of the precursors of UII, SS1 and related peptides are globally similar (Shen et al, 1982;Ohsako et al, 1986;Tostivint et al, 1996;Coulouarn et al, 1998Coulouarn et al, , 1999. Nevertheless, characterization of the cDNA encoding the UII precursor has shown that prepro-UII and prepro-SS1 do not exhibit appreciable sequence identity (Ohsako et al, 1986;Coulouarn et al, 1998Coulouarn et al, , 1999 and hence, it was concluded that the UII and SS1 precursors were probably not derived from a common ancestral gene.…”
Section: Evolutionary Relationships Between Somatostatin-and Urotensimentioning
confidence: 99%
“…10;Veber et al, 1979;Flohr et al, 2002;Labarrère et al, 2003;Chatenet et al, 2004), so that UII has been first described as a somatostatin-like peptide (Pearson et al, 1980). In addition, it has been found that the organization of the precursors of UII, SS1 and related peptides are globally similar (Shen et al, 1982;Ohsako et al, 1986;Tostivint et al, 1996;Coulouarn et al, 1998Coulouarn et al, , 1999. Nevertheless, characterization of the cDNA encoding the UII precursor has shown that prepro-UII and prepro-SS1 do not exhibit appreciable sequence identity (Ohsako et al, 1986;Coulouarn et al, 1998Coulouarn et al, , 1999 and hence, it was concluded that the UII and SS1 precursors were probably not derived from a common ancestral gene.…”
Section: Evolutionary Relationships Between Somatostatin-and Urotensimentioning
confidence: 99%
“…The composition of the peptide from peak 3 indicated probable identity with prosomatostatin-(1-63)-peptide. With the exception of a slightly high value for glutamic acid/glutamine and a slightly low value for proline, the agreement between the composition measured and that predicted from the nucleotide sequence of the prepro- somatostatin gene (Shen et al, 1982;Shen & Rutter, 1984) was good. Cleavage of prosomatostatin-(1-63)-peptide with Armillaria mellea proteinase generated five peptide fragments, which were separated by reversephase h.p.l.c.…”
Section: Concentrations Of Regulatory Peptides In the Tumour Extractmentioning
confidence: 51%
“…Tumours in which somatostatin-producing D-cells represent a majority cell type ('somatostatinomas') are rare, but have been found most often in the pancreas (Ganda et al, 1977;Larsson et al, 1977;Krejs et al, 1979;Pipeleers et al, 1979;Wright et al, 1980). The structure of the biosynthetic precursor of somatostatin (preprosomatostatin) in the human may be deduced from the nucleotide sequence of a cloned cDNA prepared from a human pancreatic tumour (Shen et al, 1982), and the structure of the gene has been determined from DNA fragments from a human genomic library (Shen & Rutter, 1984). Human preprosomatostatin is a protein of 116 amino acids that contains the sequence of somatostatin-14 at its C-terminus.…”
Section: Introductionmentioning
confidence: 99%
“…(Lamberts 1988, Schettini 1991, Martel et al 2012. SST gene is transcribed to yield the pre-pro somatostatin-encoding mRNA (Shen et al 1982, Naylor et al 1983, Shen & Rutter 1984, which is subsequently translated and the protein is processed to give rise to SST, an active peptide of 28 amino acids (Schally et al 1980, Brown et al 1981, which is commonly further processed into a shorter active variant of 14 amino acids, generally named SST-14 or simply SST (Epelbaum 1986, Martel et al 2012.…”
Section: Somatostatin and Its Receptorsmentioning
confidence: 99%